What is the optimal biological therapy for moderate to severe ulcerative colitis: a systematic review and network meta-analysis - Huang, Longbin; Kong, Chen; Yue, Ningning; Zhao, Hailan; Zhang, Yuan; Tian, Chengmei; Mai, Zhiliang; Wei, Daoru; Shi, Ruiyue; Yao, Jun; Wang, Lisheng; Li, Defeng (Frontiers in Pharmacology, 2025)
ObjectiveThe biologics for moderate to severe ulcerative colitis (UC) have expanded with an increasing array. We performed an updated network meta-analysis to evaluate and compare the relative efficacy and safety profiles of biologics in moderate to severe UC.DesignWe searched literature to 18 May 2024, to identify eligible studies. The clinical remission, clinical response, or endoscopic improvement, stratified by previous exposure or naive to biologics, and safety were assessed. A network meta-analysis was performed through the bayesian model, obtaining pairwise relative ratios (RR) and 95% confidence intervals (CI). The surface under the cumulative ranking probabilities (SUCRA) was used to rank the included agents for each outcome.ResultsA total of 23 trials (10,839 patients) were included. In induction therapy, based on achieving clinical remission and endoscopic improvement, infliximab 5 mg/kg ranked first. For clinical response, ustekinumab 6 mg/kg superior to other drugs. Infliximab 5 mg/kg demonstrated superior efficacy in biologic-naive patients, whereas ustekinumab 6 mg/kg was the most effective in biologic-exposed patients. No significant differences between active interventions were observed when assessing safety outcomes, except for visilizumab. In maintenance therapy, for clinical remission and endoscopic improvement, vedolizumab 108 mg every other week and vedolizumab 300 mg every 4 weeks ranked first respectively, with infliximab 5 mg/kg performed best in achieving clinical response. Regarding safety ranking, golimumab 100 mg was the lowest.ConclusionIn this network meta-analysis, infliximab and vedolizumab emerged as the most effective biologics for inducing and maintaining efficacy outcomes for patients with UC. Most drugs were found to be safe and well-tolerated, with ustekinumab and mirikizumab exhibiting particularly favorable safety profiles.